2011
DOI: 10.1007/s11515-011-1080-3
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins: Molecules with assorted functions

Abstract: Heat shock proteins (Hsps) or molecular chaperones, are highly conserved protein families present in all studied organisms. Following cellular stress, the intracellular concentration of Hsps generally increases several folds. Hsps undergo ATP-driven conformational changes to stabilize unfolded proteins or unfold them for translocation across membranes or mark them for degradation. They are broadly classified in several families according to their molecular weights and functional properties. Extensive studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 197 publications
(207 reference statements)
0
13
0
Order By: Relevance
“…In addition to their function as molecular chaperones, they function in protein disaggregation and protein degradation when removal of potentially harmful polypeptides arising from misfolding, denaturation, or aggregation are important for the maintenance of cellular homeostasis. The mechanism for rescuing proteins from aggregation is proposed to include the cooperation HSP100 (Kregel, 2002;Sarkar et al, 2011). HSPs are typically induced when cells are exposed to various types of environmental stresses.…”
Section: Biological or Biochemical Functions Of Flood-and Heat-responmentioning
confidence: 99%
“…In addition to their function as molecular chaperones, they function in protein disaggregation and protein degradation when removal of potentially harmful polypeptides arising from misfolding, denaturation, or aggregation are important for the maintenance of cellular homeostasis. The mechanism for rescuing proteins from aggregation is proposed to include the cooperation HSP100 (Kregel, 2002;Sarkar et al, 2011). HSPs are typically induced when cells are exposed to various types of environmental stresses.…”
Section: Biological or Biochemical Functions Of Flood-and Heat-responmentioning
confidence: 99%
“…The majority of chaperone proteins identified were part of the chaperonin-containing TCP1 complex (CCT complex), which is composed of eight unique subunits that are stacked like two donuts on top of each other to create a barrel. It is thought to primarily fold and stabilise cytoskeletal proteins due to the continuous presence of tubulin and actin in the CCT complex (Sarkar et al 2011). The CCT complex shows a unique plasma membrane localisation (bull; Byrne et al 2012, boar;Belleannee et al 2011, human;Redgrove et al 2011 and mouse;Dun et al 2011) in spermatozoa and has been shown to associate with proteins of zona-binding affinity.…”
Section: Chaperone-related Proteins Correlated With Ram Sperm Functiomentioning
confidence: 99%
“…Hsps or stress proteins are also known as molecular chaperones, because they are synthesized in increased amounts after brief exposure of cells to an elevated temperature, or a variety of other stresses such as irradiation, viral infection, oxidative stress, etc. [14]. They represent groups of ubiquitous and highly conserved protein families which utilize ATPs to stabilize unfolded proteins, or unfold them for translocation through membranes, or mark them for degradation [14].…”
Section: Heat Shock Proteins and Agingmentioning
confidence: 99%